Optimal sensors and actuators placement for large-scale unstable systems via restricted genetic algorithm. Issue 8 (6th November 2017) - Seyed Sakha, Masoud; Shaker, Hamid Reza
Abstract : Purpose: One of the fundamental problems in control systems engineering is the problem of sensors and actuators placement. Decisions in this context play a key role in the success of control process. The methods developed for optimal placement of the sensors and actuators are known to be computationally expensive. The computational burden is significant, in particular, for large-scale systems. The purpose of this paper is to improve and extend the state-of-the-art methods within this field. Design/methodology/approach: In this paper, a new technique is developed for placing sensor and actuator in large-scale systems by using restricted genetic algorithm (RGA). RGA is a kind of genetic algorithm which is developed specifically for sensors and actuator placement. Findings: Unlike its other counterparts, the proposed method not only supports unstable systems but also requires significantly lower computations. The numerical investigations have confirmed the advantages of the proposed methods which are clearly significant, in particular, in dealing with large-scale unstable systems. Originality/value: The proposed method is novel, and compared to the methods which have already been presented in literature is more general and numerically more efficient.